Strengthening the Role of Parents as Role Models in Fostering Religious Values in Children - Joan Herly Herwawan; Hery Jotlely; Maria Nindatu; Fandro Armando Tasiijawa; Zasendy Rehena; Petrosina Waremra (Karya Kesehatan Siwalima, 2026)
Parents play an important role in fostering children’s religious values through spiritual practices and role modeling within the family. This community engagement program aimed to strengthen parents’ knowledge and awareness of their role in supporting children’s spiritual development. Twenty Christian parents from the Wokaley Fellowship participated in a participatory educational program consisting of a pre-test, interactive education, group discussion, question-and-answer sessions, and a post-test. The program emphasized parental role modeling, shared responsibility between fathers and mothers, and the integration of Christian values into daily family life. Participants’ knowledge scores increased from 45% at pre-test to 100% at post-test, representing an increase of 55 percentage points. Participants also reflected on family spiritual practices and shared parental responsibility for faith formation. These findings suggest that participatory education may strengthen parental knowledge; however, follow-up evaluation is needed to assess sustained changes in family spiritual practices.